Effects of rice husk biochar on nutrient uptake and yield ofleafy vegetables: a review - Mosahrrof, Mehnaz; Siti Hasma; Uddin, Md Kamal; Shamsuzzaman, Sm; Mahmud, Md. Hasan; Islam, Md Rafiqul; Abubakar, Ahmed; Ibrahim, Nasir Adam; Hossain, ABM Sharif (Green Wave Publishing of Canada, 2022)
Green leafy vegetables have been used since ancient times as a food source because they contain many nutrients and minerals that help for growth and maintaining human health. The objective of this study is to sumarize the effect of rice husk biochar on the selected leafy vegetables. The selected leafy vegetables are spinach (Spinacia oleracea L.), cabbage (Brassica chinensis L.), lettuce (Lactuca sativa L.), Chinese cabbage (Brassica rapa chinensis),Amaranth (Amaranthus viridis L.). Day by day the demand of leafy vegetables is increasing due to consume by many people. To fulfill this demand, the production of leafy vegetables should be increased. Various organic amendments such as rice husk biochar (RHB) can be used to increase the yield. RHB is one of the soil amendments that contain nutrients which is importantforsoil health and crop production. Although characteristics of RHB are also related to other factors such as pyrolysis heating rate and residence time, its performance for specific applications (e.g. carbon sequestration, pH amendment) can be manipulated through adjustingthe pyrolysis temperature. Recent studies show the success of multi-application of biochar thataffect the soil chemical and physical properties, plant growth and yield of vegetables. This review summarizes nutrient uptake and yield of some leafy vegetables which were influenced by rice husk biochar.